National And International Legal Protection For Judicial Detainees In Jordan - حمزة الدغمي (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research examines the legal protection of judicial detainees in the Jordanian legal system in accordance with domestic and international legislation. Through an analytical study of domestic legislation and international law, the research focuses on the legal basis of judicial detention by defining its concept and legal nature. It also highlights the duration of judicial detention and the authority responsible for it as a pre-trial procedure. In addition, the research discusses judicial detention in accordance with constitutional rules as well as the obligations imposed by international law. Finally, the research discusses judicial oversight of judicial arrest decisions. The research uses the descriptive method and the legal analytical approach. The research combines theory and practice, by reviewing judicial applications of judicial detention in the Jordanian judiciary. The research concluded several results, the most important of which is that judicial detention is an exceptional measure, the Public Prosecution’s authority to arrest has been restricted in terms of the type of crime and its punishment, the purpose of the detention, and the period granted for the detention. The research recommends separating the authority to investigate from the authority to indict, so that the Public Prosecution is granted the authority to indict, and the investigative authority is entrusted to independent judges with a high degree of experience and legal knowledge.